2020
DOI: 10.1007/s00405-020-06418-5
|View full text |Cite
|
Sign up to set email alerts
|

Differences in men and women suffering from CRSwNP and AERD in quality of life

Abstract: Purpose While the overall impact of chronic rhinosinusitis (CRS) on patients’ health is diverse, many affected individuals have a substantially impaired quality of life (QoL). The aim of this study was to evaluate the impact of sex-associated differences specifically in the subgroups of CRS with nasal polyps (CRSwNP) and aspirin-exacerbated respiratory disease (AERD) by assessing QoL parameters in women and men separately. Methods In a retrospective single-center study, 59 patients with CRSwNP (39 males and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…In our study the male to female ratio was 1:1.2, 18(45%) males, 22(55%) females. This is in accordance with the studies by Qamar S et al, Alshoabi SA, Bartosik TJ and Khan M, where the disease was found to be more prevalent in females as compared to males [7][8][9][10] .…”
Section: Discussionsupporting
confidence: 93%
“…In our study the male to female ratio was 1:1.2, 18(45%) males, 22(55%) females. This is in accordance with the studies by Qamar S et al, Alshoabi SA, Bartosik TJ and Khan M, where the disease was found to be more prevalent in females as compared to males [7][8][9][10] .…”
Section: Discussionsupporting
confidence: 93%
“…11 Bartosik et al found no sex differences in QoL scores or nasal polyp prevalence at a single institution. 12 In contrast, Mendolia-Loffredo et al investigated sex differences in computed tomography (CT), endoscopy, and QoL at a single institution and stated that females had lower baseline and postoperative QoL scores. 13 Lal et al noted that females had better baseline CT Lund-Mackay scores but worse 22-item Sino-Nasal Outcome Test (SNOT-22) scores.…”
mentioning
confidence: 99%
“…Most prior clinical studies exhibit predominantly male enrollment, but recent research has emphasized epidemiologic and physiologic differences between male and female patients 11 . Bartosik et al found no sex differences in QoL scores or nasal polyp prevalence at a single institution 12 . In contrast, Mendolia‐Loffredo et al investigated sex differences in computed tomography (CT), endoscopy, and QoL at a single institution and stated that females had lower baseline and postoperative QoL scores 13 .…”
mentioning
confidence: 99%
“…9 Other authors, however, noted no differences in SNOT-20 scores between genders. 11 Evaluation using other patient health-related QoL measures (HRQOL) yield similar results. At least 1 study still found that women scored worse than men on the 36-Item Short Form Survey and EuroQol-5D (EQ-5D) (n = 93), 12 but Phillips et al in a larger study found no difference between men and women on the EQ-5D despite women in the same patient population reporting worse SNOT-22 scores (n = 500).…”
Section: Discussionmentioning
confidence: 75%